Sistem Keamanan Kendaraan Bermotor Menggunakan SMS dengan GPS Tracking Berbasis Arduino - Sumardi, Sumardi (METIK, 2019)
Motorized vehicles are objects that are in great demand by thieves so that cases of theft are still common, this is due to a lack of a security system on motorized vehicles. Standardization of security on motorized vehicles is to use only the ignition key and only a part of them are equipped with additional security such as an alarm in middle to upper class motor vehicles. The manufacturer's standard remote alarm generally only uses alarm speakers to provide signals in the form of sound, so the need for an additional security system for motorized vehicles is deemed necessary to prevent motor vehicle theft. This security system project is based on the Arduino microcontroller and prioritizes tracking the perpetrator of theft through GPS Tracking which is known by the location link of the perpetrator of the theft sent via SMS and we can turn off the machine through instructions that we give via SMS with a certain format.